Understanding the Barriers to Use of Free, Proactive Telephone Counseling for Tobacco Dependence - Sheffer, Christine E. (2011)
We sought to gain an empirical and practical understanding of the barriers experienced by Arkansas Mississippi Delta residents to using the free telephone counseling (quitline) for tobacco dependence. Barriers included lack of knowledge about the quitline, lack of trust in the providers, as well as multiple root causes to seeking and achieving abstinence from tobacco including issues related to the poor socio-economic context and concerns about negative health effects of quitting. A strong belief in the role of faith in the process of quitting was expressed. Participants suggested strategies for increasing knowledge and trust levels, but were not hopeful about addressing root causes. Given the considerable resources being allocated to quitlines and the burden of tobacco use and disease in lower socioeconomic and minority groups, understanding utilization of quitlines by these groups has implications for policy development, the promotion of quitlines, and the provision of alternate tobacco treatment services.